2003
DOI: 10.1159/000069017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Olive Oil Emulsions on Dentin Demineralization in vitro

Abstract: The effect of two different concentrations of olive oil emulsions on development of artificial caries-like dentin lesions under severe demineralizing conditions was investigated. Bovine dentin samples (n = 180) were ground flat, polished, divided into four groups, and subjected to three demineralization cycles per day. Samples were stored in one of the following solutions for 5 min prior to demineralization in a buffer solution (pH 5): Group 1: 50% oil emulsion (olive oil and distilled water); group 2: 5% oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 16 publications
0
27
1
Order By: Relevance
“…In the buffer II group, the specimens were immersed in 30 ml of 50 m M acetate buffer solution containing 2.2 m M CaCl 2 , 2.2 m M KH 2 PO 4 , at pH 5.0, for 7 days [ten Cate and Duijsters, 1982;Damen et al, 1998]. In the TEMDP group, the specimens were immersed in 30 ml of 50 m M lactate buffer containing 3 m M CaCl 2 , 3 m M KH 2 PO 4 , 6 M tetraethyl methyl diphosphonate and traces of thymol, at pH 5.0, for 7 days [Buskes et al, 1985;Buchalla et al, 2003]. In all in vitro models, the specimens were separately immersed in unstirred solutions or gel at 37 ° C. Table 1 summarizes the degrees of saturation with respect to dentine minerals, pH and exposure time.…”
Section: In Vitro Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the buffer II group, the specimens were immersed in 30 ml of 50 m M acetate buffer solution containing 2.2 m M CaCl 2 , 2.2 m M KH 2 PO 4 , at pH 5.0, for 7 days [ten Cate and Duijsters, 1982;Damen et al, 1998]. In the TEMDP group, the specimens were immersed in 30 ml of 50 m M lactate buffer containing 3 m M CaCl 2 , 3 m M KH 2 PO 4 , 6 M tetraethyl methyl diphosphonate and traces of thymol, at pH 5.0, for 7 days [Buskes et al, 1985;Buchalla et al, 2003]. In all in vitro models, the specimens were separately immersed in unstirred solutions or gel at 37 ° C. Table 1 summarizes the degrees of saturation with respect to dentine minerals, pH and exposure time.…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…The other half of the specimens was additionally cut and hand polished plane-parallel from both cut sides with water-cooled silicon carbide disks (320-, 600-, and 1,200-grade papers, ANSI grit; Buehler) to a thickness of 138 8 7.6 m. After the immersion of the specimens in ethylene glycol (Sigma-Aldrich, Steinheim, Germany) for 24 h in order to avoid shrinkage during X-ray exposure due to desiccation [Buchalla et al, 2003], micrographs of each section together with an aluminum calibration step wedge with 14 steps were taken. High-speed holographic film (SO 253; Kodak AG, Stuttgart, Germany) was exposed with Ni-filtered quasimonochromatic Cu K ␣ X-rays ( = 0.154 nm) from a 1 !…”
Section: Transverse Microradiographymentioning
confidence: 99%
See 2 more Smart Citations
“…Though knowledge on lipids in the acquired pellicle is based on only these two publications [Slomiany et al, 1986[Slomiany et al, , 1990, their possible impact on the protective properties has been discussed extensively [Hannig and Joiner, 2006]. Furthermore, several in vitro studies neglecting the in situ pellicle indicated that vegetable oil mouthrinses or olive oil-containing preparations might form a protective coating on dental hard tissues decreasing erosive mineral loss [Buchalla et al, 2003;Wiegand et al, 2007]. Irrespective of the lipid composition the pellicle is regarded as a semi-permeable barrier and buffer reducing erosive mineral loss [Hara et al, 2006;Hannig et al, 2009].…”
mentioning
confidence: 99%